DESIGN OPTIMIZATION OF OMNIDIRECTIONAL MIRROR OF AUTONOMOUS MOBILE ROBOT FOR SURVEILLANCE CAMERA COMPONENT USING QUALITY FUNCTION DEPLOYMEN METHOD - Immawan, Taufiq; Dewa Yasa, Aland (Jurnal Teknologi, 2020)
Currently, the use of automation has become a useful tool to monitor manufacture in improving work efficiency and safety. One way the use of automation is applied in the monitoring process is the Autonomous Mobile Robot (AMR) which is often used to recognize objects with its camera sensors based on the direction of motion, position, and shape of the objects. However, conventional camera sensors on AMR have a limited point of view on the object. This problem can be solved by adding an omnidirectional mirror on the camera, which enables the camera to capture objects with a 360 degree view in one frame. However, the addition of omnidirectional mirror in general may lead to high cost production. Therefore, this study aims to design an omnidirectional mirror that is cost-effective and suitable to be integrated with the cameras. The design process of this study uses a Quality Function Deployment (QFD) approach to identify the best features related to the material and arrangement of the omnidirectional mirror’s angle. The proposed result of the omnidirectional mirror design hopefully will capture a better and more optimal quality of the object at a lower cost. In practice, AMR added with omnidirectional mirror can raise the efficacy of the surveillance system by capturing clearer images. Consequently, the use of AMR can contribute further to various sectors in life, including manufacturing processes, home industries, traffic, and many more.